Antibacterial efficacy and antibiotic sensitivity augmentation potential of selected traditional medicinal plant extracts against Vibrio cholerae O1 E1 Tor Ogawa - Pruthviraj Chavan; Kamakshi Naik; Soumika Ghosal; Rajitha Charla; Rajalakshmi Patil; Jyoti N. Guruputranavar; Vishal S. Patil; Darasaguppe R. Harish; Subarna Roy (Future Journal of Pharmaceutical Sciences)
Abstract Background The leaves of Psidium guajava (PGAE), fruit peel of Punica granatum (PGRPE), and the bark of Careya arborea (CAE) are widely used traditional medicinal plants for treating diarrheal diseases across India. Our previous studies showed that the hydroalcoholic extracts of these plant parts inhibit the cholera toxin activity. Hence, this study is framed to investigate these extracts for anti-Vibrio cholerae activity and their ability to augment antibiotic sensitivity through a combination of in vitro and computational methods. The hydroalcoholic extracts of PGAE, PGRPE, and CAE were tested for antibacterial activity against Vibrio cholerae by minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and virulence gene expression studies by reverse transcriptase-polymerase chain reaction (RT-PCR). Further, antibacterial activity in combination with selected antibiotics was performed by disk diffusion method. The possible mode of action of these extracts was predicted using docking and molecular dynamics studies on selected virulence factors of Vibrio cholerae. Results All three plant extracts depicted antibacterial activity at different degrees. CAE showed MIC and MBC at 1.25 mg/mL and 10 mg/mL, PGAE at 1.25 mg/mL and 5 mg/mL; and PGRPE at 2.5 mg/mL and 10 mg/mL, respectively. RT-PCR confirmed these extracts significantly inhibited the expression of virulence genes like Flagellin A (FlaA), Vibrio polysaccharide synthesis transcription regulator (VpsT), and Lux Operon (LuxO). Further, the computational studies predicted that phytocompounds of these plants pose stable interaction with AphA, AphB, and ToxT playing the key role in inhibiting the expression of virulence factors. Conclusion The results emphasize that these plant extracts potentially inhibit the growth of Vibrio cholerae, decrease the expression of virulence gene, and enhance the sensitivity of certain conventional antibiotics.